The Impact of Sales Growth and Digital Revenue on Financial Performance in Digital Companies in Indonesia - Ario Purdianto; Auryn Shafarina (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the influence of Sales Growth and Digital Revenue on Financial Performance in digital companies in Indonesia for the period 2022–2024. The rapid development of the digital economy is not always accompanied by increased company profitability, so it is necessary to examine the factors that influence financial performance. This study uses a quantitative approach with a multiple linear regression method on 60 digital companies selected using a purposive sampling technique. Financial Performance is measured using Return on Equity (ROE), Sales Growth is measured based on annual revenue growth, while Digital Revenue is measured using Digital Revenue Share (DRS), which is the ratio of digital revenue to total company revenue.The results of the study indicate that Sales Growth has a positive and significant effect on ROE. Digital Revenue also has a positive and significant effect on ROE and has a more dominant influence than Sales Growth. Simultaneously, Sales Growth and Digital Revenue have a significant effect on Financial Performance with an Adjusted R Square value of 0.895, indicating that 89.5% of the variation in ROE can be explained by these two independent variables. These findings indicate that successful digital monetization through increased digital revenue is a key factor in improving the financial performance of digital companies.